Biomarkers for invasive aspergillosis: the challenges continue. (March 2014) - Johnson, Gemma; Ferrini, Arianna; Dolan, Stephen K; Nolan, Tania; Agrawal, Samir; Doyle, Sean; Bustin, Stephen A
The incidence of invasive aspergillosis (IA), an opportunistic infection in immunocompromised individuals, is rising, but its early diagnosis remains challenging and treatment options are limited. Hence there is an urgent need to improve existing diagnostic procedures as well as develop novel approaches. The clinical usefulness of galactomannan and β-d -glucan, widely used assays detecting cell-wall antigens of Aspergillus, is unclear and depends on clinicians' awareness of their practical limitations. This leaves room for new methods that utilise genomic, proteomic and metabolomics approaches as well as novel detection procedures, for example point-of-care lateral-flow devices. Each of these strategies has its own limitations and it is likely that a combination of methods will be required to achieve optimal performance for the diagnosis of IA and subsequent appropriate patient management.